1996
DOI: 10.1108/02689239610146508
|View full text |Cite
|
Sign up to set email alerts
|

The effects of demographics on determinants of perceived health‐care service quality

Abstract: Notes that previous research suggests the components of perceived service quality are industry specific, and that calls have been made for academics to integrate their theory into practice. Investigates the effects of demographic factors on users and observers of perceived hospital quality. Reports results suggesting perceived quality is industry specific, users and observers differ in their perceptions of hospital quality and demographic factors do make a difference in perceived hospital quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 19 publications
0
60
2
1
Order By: Relevance
“…Several applications of SERVQUAL have been accounted for while it has been tested and used to quantify service quality in different contexts, like banking sector (Ehigie, 2006;Karatepe et al, 2005;Mels et al, 1997;Poolthong and Mandhachitara, 2009;Jabnoun and Al-Tamimi, 2003;Zhou et al, 2002), hospitality industry (Nadiri and Hussain, 2005b;Butler et al, 1996;Mei et al, 1999;O'Neill et al, 1994), insurance (Tsoukatos and Rand, 2006), restaurant (Qin et al, 2010) and internet marketing (Long and McMellon, 2004).…”
Section: Perceived Service Qualitymentioning
confidence: 99%
“…Several applications of SERVQUAL have been accounted for while it has been tested and used to quantify service quality in different contexts, like banking sector (Ehigie, 2006;Karatepe et al, 2005;Mels et al, 1997;Poolthong and Mandhachitara, 2009;Jabnoun and Al-Tamimi, 2003;Zhou et al, 2002), hospitality industry (Nadiri and Hussain, 2005b;Butler et al, 1996;Mei et al, 1999;O'Neill et al, 1994), insurance (Tsoukatos and Rand, 2006), restaurant (Qin et al, 2010) and internet marketing (Long and McMellon, 2004).…”
Section: Perceived Service Qualitymentioning
confidence: 99%
“…They are determined by the degree of control exercised between the patient and the provider. Two prominent approaches are the paternalistic model, with the physician having the dominant role, and the informative model in which the key responsibility of the physician is to provide the medical expertise [4,12,17]. Another widely advocated interpretation of the doctor-patient relationship is the model of shared-decision-making.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have shown that the physician-patient relationship can play a crucial role in directly influencing patient's health and well-being through the patient's sense of feeling understood as well as indirectly through continuity of care and adherence to treatment regimen [3,6,8,16]. Physicians' professional credibility and competence, as well as the appropriateness of communication, significantly determine patients' psychological status, physiological symptoms and functional outcomes [6,[17][18][19]. The accumulated evidence indicates that patient-centered communication, including informationgiving and information-seeking behavior and patient involvement in the treatment process, can alleviate patients' feelings of uncertainty and can even affect the healing process [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the tertiary hospital organization, several factors such as patients-related, employee-related and employer-related factors interact to affect the quality of care the patients received. [12]…”
Section: Introductionmentioning
confidence: 99%